2006
DOI: 10.2307/20111834
|View full text |Cite
|
Sign up to set email alerts
|

Finance and Income Inequality: What Do the Data Tell Us?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
286
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(312 citation statements)
references
References 7 publications
19
286
1
6
Order By: Relevance
“…Their sample consists of 65 countries over the period . Using a similar model for a larger group of countries (83) but a shorter sample period , Clarke et al (2006) also find that financial development reduces inequality. Kappel (2010), who uses a sample of 59 countries for a cross-country analysis and 78 countries for a panel analysis over the period 1960 to 2006, concludes that financial development reduces income inequality for high-income countries, but is not significant for low-income countries.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Their sample consists of 65 countries over the period . Using a similar model for a larger group of countries (83) but a shorter sample period , Clarke et al (2006) also find that financial development reduces inequality. Kappel (2010), who uses a sample of 59 countries for a cross-country analysis and 78 countries for a panel analysis over the period 1960 to 2006, concludes that financial development reduces income inequality for high-income countries, but is not significant for low-income countries.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Several related studies using panel data or cross-country data, such as Li et al (1998), Clarke et al (2006), and Beck et al (2007), have empirically demonstrated that as the financial sector fully develops, income inequality decreases. No previous study, however, has examined the effect of financial integration on the relationship between financial development and inequality.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Clarke et al (2006) identify three distinct hypotheses that are dominant in the literature: the "inequality-widening hypothesis", the "inequality-narrowing hypothesis" carried by Galor and Zeira (1993) and Banerjee and Newman (1993) and the "inverted-Uhypothesis" by Greenwood and Jovanovic (1990).…”
Section: Figure 1 Financial Development Economic Growth Inequalitymentioning
confidence: 99%